2019
DOI: 10.1186/s12886-019-1131-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of retinal layer changes with vision gain in diabetic macular edema during conbercept treatment

Abstract: Backgrounds To assess the changes in individual retinal layer thickness and visual function associated with gains in visual acuity after an intravitreal conbercept injection in the diabetic macular edema (DME) on spectral domain optical coherence tomography (SD-OCT) and microperimetry during 1-year follow-up. Methods Retrospective observational study. Twenty patients with clinically significant DME in the study eye were imaged by SD-OCT every 3 months and MP1 microperim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…The cumulative mean number of injections was 6 (5 studies with 5 treatment arms). Two studies each reported the mean number of injections for conbercept 1 dose at baseline (1q4w) followed by PRN regimen (5.6 46 and 6.8 45 ) and conbercept 3q4w followed by PRN regimen (6.6 36 and 6.6 47 ) ( Figure S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…The cumulative mean number of injections was 6 (5 studies with 5 treatment arms). Two studies each reported the mean number of injections for conbercept 1 dose at baseline (1q4w) followed by PRN regimen (5.6 46 and 6.8 45 ) and conbercept 3q4w followed by PRN regimen (6.6 36 and 6.6 47 ) ( Figure S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Triamcinolone acetonide has a strong antiallergic effect and lasting for a long time. After intravitreal injection, it can block the proliferation of endothelial cells and angiogenesis, achieving the effect of treating fundus vascular diseases and the best-corrected visual acuity of patients [ 24 , 25 ]. In addition, its action inhibits the production of prostaglandins, downregulates VEGF expression, and has a synergistic effect with conbercept [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Conbercept (KH902; Chengdu Kanghong Biotechnology Co., Ltd., Sichuan, China), a new anti-VEGF reagent, has been developed and used in clinical treatment. 17 Previous studies have shown that conbercept can improve a variety of clinical symptoms, such as best corrected visual acuity (BCVA), central foveal thickness (CFT), and choroidal neovascularization area. 18 Conbercept has been used in the treatment of diabetic macular edema, 17 wet age-related macular degeneration, 19 chronic central serous chorioretinopathy, 20 and proliferative diabetic retinopathy.…”
Section: Introductionmentioning
confidence: 99%